Features of growth, development and formation of winter wheat productivity depending on cultivation technologies - A. B. Ismailov; D. S. Magomedova; M. G. Muslimov; N. A. Yusufov; D. M. Ramazanov; Sh. K. Omarov (Зерновое хозяйство России)
The current paper has presented the study results on the effect of growth regulators and bacterial products on productivity of various winter wheat varieties zoned in the North Caucasus Federal District in 2017–2019. The trials were carried out on meadow-chestnut soil of the flat irrigated area of Dagestan. There has been given an analysis of the indicators influencing the formation of the future productivity, such as field germination of seeds, the length of the phenological phases of growth and development of the crop in the autumn and spring vegetation and the dependence on the choice of growth-stimulating and bacterial preparations, as well as the varietal potential of winter wheat. There has been established that the use of growth regulators and bacterial preparations before sowing, as well as spraying plants in the tillering phase, significantly affects the elements of the crop structure and, ultimately, the biological productivity. The purpose of the current work was to study the effect of various growth regulators and bacterial products on the characteristics of growth, development and formation of productivity of winter wheat varieties, as well as to determine the comparative productivity of zoned varieties. As a result of the conducted trials, there has been found out that the largest productivity of winter wheat varieties was formed in the variant with the use of the bacterial product ‘Azofit’ during pre-sowing seed treatment (application rate of 1 l/t of seeds) together with the growth stimulator ‘Kostando, KE’ during spraying in the tillering phase (application rate of 0.2 l/ha). The comparative estimation of varieties’ productivity showed a significant difference of the variety ‘Sila’, which demonstrated an advantage over other varieties in all variants of the trial. Thus, with the optimal variant established by us using growth stimulants ‘Azofit’ and ‘Kostando, KE’ the productivity level of this variety was 5.0 t/ha.